Usefulness of endoscopic ultrasound-guided fine needle aspiration for splenic parenchyma in patients suspected of having primary splenic malignant lymphoma - Niiya, Fumitaka; Takano, Yuichi; Azami, Tetsushi; Kobayashi, Takahiro; Maruoka, Naotaka; Kabasawa, Nobuyuki; Harada, Hiroshi; Norose, Tomoko; Ohike, Nobuyuki; Nagahama, Masatsugu (Endoscopy International Open, 2021)
Background and study aims The diagnosis of malignant lymphoma (ML) is sometimes difficult, especially in patients with primary splenic malignant lymphomas (psML) which have no lymph nodes capable of acting as the biopsy target. We carried out endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) for “splenic parenchyma” in patients suspected of having a psML, even without any obvious neoplastic lesions in the spleen.Patients and methods A retrospective study using medical records was conducted of eight patients suspected of having a psML that received EUS-FNA for the splenic parenchyma between January 2016 and January 2019. Data analyzed included clinical background, EUS-FNA procedure (puncture needle/route), diagnostic ability (pathological/flow cytometry [FCM]), and complications.Results EUS-FNA was performed from the stomach in all eight cases, and no patients had complications. As a result of splenic parenchymal biopsy found on EUS-FNA, 75 % of patients (6/8) were histologically diagnosed with MLs, monoclonality of B-cells was identified in all cases (8/8) with FCM, and all patients (8/8) were definitively diagnosed with psMLs.Conclusion EUS-FNA for “splenic parenchyma” is useful for patients with spML, even if they have no obvious neoplastic lesions in the spleen.